Cis versus Trans: The Coordination Environment about the Tin(IV) Atom in Spirocyclic Amino Alcohol Derivatives. Issue 72 (28th November 2018) - Glowacki, Britta; Pallach, Roman; Lutter, Michael; Roesler, Fabian; Alnasr, Hazem; Thomas, Cedreric; Schollmeyer, Dieter; Jurkschat, Klaus
Abstract: The syntheses of amino alcohols MeN(CH2 CH2 CMe2 OH)2 (1 ), MeN(CMe2 CH2 OH)(CH2 CMe2 OH) (2 ), MeN(CH2 CH2 CH2 OH)(CH2 CMe2 OH) (3 ), MeN(CH2 CH2 CMe2 OH)(CH2 CMe2 OH) (4 ), MeN(CH2 CH2 CMe2 OH)(CH2 CH2 OH) (5 ), and MeN(CH2 CH2 OH) (CH2 CH2 CH2 OH) (6 ) as well as spirocyclic tin(IV) alkoxides spiro ‐[ n BuN(CH2 CMe2 O)2 ]2 Sn (7 ), spiro ‐[MeN(CH2 CH2 CMe2 O)2 ]2 Sn (8 ), spiro ‐[ para ‐FC6 H4 N (CH2 CMe2 O)2 ]2 Sn (9 ), spiro ‐[MeN(CMe2 CH2 O)(CH2 CMe2 O)]2 Sn (10 ), spiro ‐[MeN(CH2 CH2 CH2 O)(CH2 CMe2 O)]2 Sn (11 ), spiro ‐[MeN(CH2 CH2 CMe2 O)(CH2 CMe2 O)]2 Sn (12 ), spiro ‐[MeN(CH2 CH2 CMe2 O)(CH2 CH2 O)]2 Sn (13 ) and spiro ‐[MeN(CH2 CH2 O)(CH2 CH2 CH2 O)]2 Sn (14 ) are reported. The compounds were characterized by 1 H, 13 C (1 –14 ) and 119 Sn (7 –14 ) NMR and IR spectroscopy, EIMS and single‐crystal XRD (2, 7 –10 and13, 14 ). Graph‐set analyses were performed for compounds [(MeNH(CMe2 CH2 OH)(CH2 CMe2 OH)][HC(O)O] (2 a ) and2 . The coordination environment about the tin(IV) centre of the spirocyclic compounds and their possible stereoisomers were analysed by DFT calculations ( spiro ‐[MeN(CH2 CMe2 O)2 ]2 Sn, 8 –10 and13 ). Abstract : Tin‐centred spirocycles : The length of the amino alcoholate chains as well as the identity of the substituents at the side chains and at the nitrogen atoms control the geometrical environment about the metal atom (e.g., cis versus trans disposition of the N atoms) in spirocyclic tin(IV) derivatives of amino alcohols (see figure).